Guidelines on Financial Systems’ Comparative Analysis (Economic and Political Thought, 2013)
The article aims to present guidelines on financial systems’ comparativeanalysis. The author focuses on the guidelines on the comparison of the sizeof financial institutions and financial markets in the analyzed countries, thelevel of accessibility of financial institutions and financial markets to a financialmarket member and the efficiency and stability of financial institutionsand financial markets. The article presents a series of indicators useful inthe conduction of a comparative analysis of the financial systems in differentcountries.